Restoring and emulsifying properties of the dried meat semi-finished product - Niemirich, Oleksandra; Pohozhykh, Mykola; Petrusha, Oksana; Havrysh, Andrey; Vasheka, Oksana (My University, 2017)
Вивчено технологічні властивості висушеного м'ясного напівфабрикату, виготовленого методом змішаного теплопідведення. На основі проведених досліджень розроблено математичну залежність комплексної характеристики сушеного м’яса від температури сушіння та ступеня дисперсності продукту. The technological properties of the dried meat semi-finished product made by the DMSF-drying (mixed heat supply) method are studied, on the basis of which the mathematical dependence of the complex characteristic of the SMC on the drying temperature and the degree of product dispersion is difficult.
Keywords: м’ясний напівфабрикат; сушіння; змішане теплопідведення; пористість; meat emulsion; semifinished; drying mixed heatpendencies; porosity; кафедра експертизи харчових продуктів; кафедра технології ресторанної і аюрведичної продукції